(untitled) (Training and Practice : Journal of Educational Sciences, 2017)
One of the consequences of the domestic social economic changes is that young people who are at secondary school appear at a very early age in the labour market. Those who are already 16 years old are entitled to work. Furthermore, voluntary work has been introduced and is applied in case of all students who are before the Matura examination - stepping out of the shield of school and family - so they appear in the world of work in different forms. The differentiation may be demonstrated in almost every area of life, but in the world of work the phenomenon of discrimination appears significantly. The young age-group is affected because of psycho-social reasons and they are concerned directly and indirectly to a great extent. Therefore it is particularly important for the young employees to gain knowledge about the discriminative phenomena which affect this adolescence age-group, thus those who are concerned may make a decision about their impressions further in the labour market; and these experiences will influence their attitude towards work as well.